2020
DOI: 10.1016/j.ebiom.2020.102999
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interleukin-6 blockade with tocilizumab on SARS-CoV-2 viral kinetics and antibody responses in patients with COVID-19: A prospective cohort study

Abstract: Background The virological and immunological effects of the immunomodulatory drugs used for COVID-19 remain unknown. We evaluated the impact of interleukin (IL)-6 blockade with tocilizumab on SARS-CoV-2 viral kinetics and the antibody response in patients with COVID-19. Methods Prospective cohort study in patients admitted with COVID-19. Serial nasopharyngeal and plasma samples were measured for SARS-CoV-2 RNA and S-IgG/N-IgG titers, respectively. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 32 publications
5
67
0
1
Order By: Relevance
“…Based on six systematic reviews that assessed tocilizumab, this IL-6 blockade agent could be beneficial in the treatment of severely ill COVID-19 patients. These findings are in line with recent cohort studies that have suggested that the IL-6 blockade does not impair the specific antibody response against SARS-CoV-2 and may help reduce the risk of death among severely ill COVID-19 patients; 82 , 83 nonetheless, they warrant further investigation in sufficiently controlled trials.…”
Section: Discussionsupporting
confidence: 88%
“…Based on six systematic reviews that assessed tocilizumab, this IL-6 blockade agent could be beneficial in the treatment of severely ill COVID-19 patients. These findings are in line with recent cohort studies that have suggested that the IL-6 blockade does not impair the specific antibody response against SARS-CoV-2 and may help reduce the risk of death among severely ill COVID-19 patients; 82 , 83 nonetheless, they warrant further investigation in sufficiently controlled trials.…”
Section: Discussionsupporting
confidence: 88%
“…Blocking antibodies or small molecules targeting IL-6 or its signal transduction pathways have been used in the clinical trials to treat COVID-19 patients ( 23 , 29 ). However, targeting IL-6 signal transduction pathways might be complicated as IL-6 activates both pro-inflammatory pathway through the soluble form of the IL-6 receptor, and anti-inflammatory pathway through the membrane-bound form of the IL-6 receptor ( 27 , 44 ). IL-8 is clearly a pro-inflammatory cytokine that may recruit neutrophils to the infected areas and has been associated with tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, hospital and ICU lengths of stay did not differ between tocilizumab and SOC [20][21][22][23][24][25][26]31,32,35,40,43 . Only one study (Eimer et al) showed that length of stay in hospital on tocilizumab was shorter than the SOC and it was able to shorten the duration of use of a ventilator.…”
Section: Discussionmentioning
confidence: 99%